ChemInform Abstract: Thermodynamic Hydricity of Transition Metal Hydrides. Issue 43 (7th October 2016) - Wiedner, Eric S.; Chambers, Matthew B.; Pitman, Catherine L.; Bullock, R. Morris; Miller, Alexander J. M.; Appel, Aaron M.
Abstract: Review: 331 refs.